Evaluation of a support and challenge framework for nursing managers in correctional and forensic health. (8th August 2013) - Newman, Claire; Patterson, Karen; Clark, Gary
<x xml:space="preserve">Abstract</x> Aim This study evaluated a framework for nursing managers which entailed supporting and challenging participants to critically analyse the effectiveness of their workplace behaviours in facilitated discussion groups using context‐laden real‐life scenarios. Background Leadership development in nursing managers has been shown to reduce burnout and promote workplace satisfaction. Method Ninety per cent of nursing managers (n = 63) employed in the organisation participated in the study. Data relating to burnout, workplace satisfaction and leadership practices were collected prior to and after participation in the support and challenge framework. Qualitative feedback was sought through a survey administered at follow‐up. Result Nursing Unit Managers were significantly less satisfied in their intrinsic domain of workplace satisfaction at follow‐up. Qualitative feedback indicated that participants experienced benefits related to networking, personal development and role development. Conclusion The experience of critiquing and challenging leadership when shared with peers who practice in a similar context was qualitatively reported as beneficial and valuable, in spite of a decrease in workplace satisfaction. Implications for nursing management Nursing manager's leadership development is a continuous process. Supporting and challenging nursing managers is likely to generate uncertainty related to self and role. The sharing and testing of this uncertainty with peers is welcomed and warrants further exploration.